Peran Motivasi Belajar Siswa Dalam Hasil Belajar Tematik Di Sekolah Dasar Tahun Ajaran 2021/2022 - ., Ryzca Siti Qomariyah; ., Mustika Kirana Putri; ., Irfan Aminullah (CV. ITTC INDONESIA, 2022)
This study aims to analyze the role of students' learning motivation in thematic learning outcomes in elementary schools. The research was conducted at SDN Kertosuko 3 with research data obtained from interviews using descriptive quantitative methods. The research was conducted by analyzing interest in learning and student learning outcomes which were calculated based on an authentic assessment system. The results of the study show that student learning motivation has an important role in student learning outcomes. this is evidenced by the acquisition of learning interest scores and the results of students' written tests.